C-Smile, COCA, and BNC: a focus on amplifiers and adjective collocations - Basthomi, Yazid; Yannuar, Nurenzia; Widiati, Utami; Martiningtyas, Rahma (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
In order to explicate a specific message from statements, amplifiers mostly collocate with particular lexical items referring to evaluation, judgment, or attitude. Using six types of amplifiers consisting of absolutely, completely, entirely, fully, totally, and utterly, the research intends to elicit kinds of adjective collocation that follow each of the amplifiers. Three different corpora of non-native and native speakers of English are used in order to see the common pattern of amplifiers and their collocations as well as to compare their use in different contexts and among users of English. The results show that the collocations are varied in the sense that each corpus provides a number of adjectives in which some of them are similar to the ones occurring in the other corpora and some others only occur in a particular corpus. Specific evaluations of amplifiers viewed from their adjective collocations fall under three basic categories of positive, negative, and neutral values. By investigating and comparing amplifiers and collocations used in non-native and native academic writings, the findings of the present study point to the fact that each amplifier constitutes specific evaluations.